D-Lactate: Implications for Gastrointestinal Diseases - Barblin Remund; Bahtiyar Yilmaz; Christiane Sokollik (MDPI AG, 2023)
D-lactate is produced in very low amounts in human tissues. However, certain bacteria in the human intestine produce D-lactate. In some gastrointestinal diseases, increased bacterial D-lactate production and uptake from the gut into the bloodstream take place. In its extreme, excessive accumulation of D-lactate in humans can lead to potentially life-threatening D-lactic acidosis. This metabolic phenomenon is well described in pediatric patients with short bowel syndrome. Less is known about a subclinical rise in D-lactate. We discuss in this review the pathophysiology of D-lactate in the human body. We cover D-lactic acidosis in patients with short bowel syndrome as well as subclinical elevations of D-lactate in other diseases affecting the gastrointestinal tract. Furthermore, we argue for the potential of D-lactate as a marker of intestinal barrier integrity in the context of dysbiosis. Subsequently, we conclude that there is a research need to establish D-lactate as a minimally invasive biomarker in gastrointestinal diseases.